Improving performances of the electrode/electrolyte interface via the regulation of solvation complexes: a review and prospect. Issue 10 (13th February 2023) - Quan, Yin; Wu, Shumin; Yang, Kerong; Hu, Ling; Zhang, Xiaojuan; Hu, Xinyi; Liang, Hongcheng; Li, Shiyou
Abstract : This minireview summarizes the effects of solvation complexes on the composition of EEI film and Li +  desolvation process from the perspective of the electrolyte and further clarifies the internal mechanism of the electrolyte composition. Abstract : The electrode/electrolyte interface (EEI) is a research hotspot in lithium-ion batteries, while the electrolyte solvation complex can be regarded as a factor that cannot be ignored in determining the performance of the EEI. From the perspective of the electrolyte solvation complex, this review summarizes the effects of solvation complexes on the composition of an EEI film and the Li + desolvation process, and further clarifies the internal mechanism of the electrolyte composition controlling solvation chemistry. Finally, combined with doubtful points that are not comprehensively considered in the regulation of solvated complexes, this review puts forward some cutting-edge views, which are of great significance for future guidance in improving the performance of lithium-ion batteries.